2002
DOI: 10.1111/1467-8276.00360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Private‐Label Invasion in Food Industries

Abstract: Using supermarket scanner data, we test a variety of hypotheses from trade journals about the invasion of private‐label food products. According to conventional industry wisdom, name‐brand firms defended their brands against new private‐label products by lowering their prices, engaging in additional promotional activities, and increasingly differentiating their products. Our empirical evidence is inconsistent with these beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 23 publications
7
84
0
1
Order By: Relevance
“…This increasing presence has deeply modified the landscape of retail competition (Ezrachi & Bernitz, 2009). As noted by Ward et al (2002), there are different points of view that could be observed, and previous researches investigated why companies produce PL goods (Bontems et al, 1999;Galizzi et al, 1997) and why retailers offer them (Mills, 1995;Dhar & Hoch, 1997;Narasimhan & Wilcox, 1998), as well as the first differentiation between PL and branded products is focused above all on the price level (Conner & Peterson, 1992;Hinloopen & Martin, 1997;Putsis, 1997).In particular, the attitude towards PL products is reinforced by price/value consciousness and smart-shopper self-perceptions, as observed by Burton et al (1998). Anyway, citing the work of Gyongyi et al (2012), the PL strategies adopted by retailers moved, with the passage of time, to other dimensions, tracing different stages.…”
Section: Brand and Private Label In Food Retailingmentioning
confidence: 75%
See 1 more Smart Citation
“…This increasing presence has deeply modified the landscape of retail competition (Ezrachi & Bernitz, 2009). As noted by Ward et al (2002), there are different points of view that could be observed, and previous researches investigated why companies produce PL goods (Bontems et al, 1999;Galizzi et al, 1997) and why retailers offer them (Mills, 1995;Dhar & Hoch, 1997;Narasimhan & Wilcox, 1998), as well as the first differentiation between PL and branded products is focused above all on the price level (Conner & Peterson, 1992;Hinloopen & Martin, 1997;Putsis, 1997).In particular, the attitude towards PL products is reinforced by price/value consciousness and smart-shopper self-perceptions, as observed by Burton et al (1998). Anyway, citing the work of Gyongyi et al (2012), the PL strategies adopted by retailers moved, with the passage of time, to other dimensions, tracing different stages.…”
Section: Brand and Private Label In Food Retailingmentioning
confidence: 75%
“…In the food industry, products marked with a brand owned or controlled by food retailer or wholesaler are not a novelty since, from the 1930', their proposal is a concrete offer, above all in US context (Call, 1967), with increasing market shares registered until now (Mathews, 1996). At the beginning these products were standard and related to few categories, even if actually they are producing a considerable pressure (Ward et al, 2002). This increasing presence has deeply modified the landscape of retail competition (Ezrachi & Bernitz, 2009).…”
Section: Brand and Private Label In Food Retailingmentioning
confidence: 99%
“…At least in part, these retailer motivations explain the general movement towards higher quality/premium private label products that frequently close the objective quality gap with manufacturer brands. This higher quality trend is in many cases attributable to the technical and production expertise of the many manufacturer brands such as Lexmark, Heinz, Hershey's, Kraft, Campbell's Soup, General Foods, and Pillsbury that quietly produce private labels as a means to take share from other manufacturer brands, utilize excess manufacturing capacity, and build closer relationships with major retailers (Dunne and Narasimhan, 1999;Kumar and Steenkamp 2007;Ward et al, 2002). Recent research suggests that consumer beliefs about real or perceived manufacturer brand sourcing of private labels is a key factor in their quality beliefs about private label products (Steenkamp et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Western retailers not only compete with national brands, but also against rival retailers' brands. Building differentiated brands from other retailers is the most effective weapon in competing against rival retail brands (Fernie & Pierrel, 1996;Burt, 2000;Ward et al, 2002;Verhoef, Nijssen, & Sloot., 2002;Colla& Dupuis, 2002;Ailawadi & Harlam, 2004). The third type of competition with own brands comes from the discounters.…”
Section: Literature Reviewmentioning
confidence: 99%